162k views
2 votes
I'm really confused about this question,
-(q+7) = -6q + 8​

I'm really confused about this question, -(q+7) = -6q + 8​-example-1
User Dorriz
by
5.2k points

1 Answer

5 votes
to solve, first distribute your negative on the left side.

-(q+7) -> -q-7

now, just balance out both sides by first adding your left q to your right q’s

-q-7 = -6+8
+q +q

-7 = -5q + 8

then, subtract your 8 from both sides

-7 = -5q + 8
-8 -8

-15 = -5q

finally, just solve for q by dividing both sides by -5

-15 = -5q
/-5 /-5

3 = q
User Bjoern Rennhak
by
4.8k points